1989
DOI: 10.1016/0304-3959(89)90048-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of attention on the intensity and unpleasantness of thermal pain

Abstract: Both experimental and clinical studies have shown that psychological manipulations, such as hypnosis, behavioral modification and cognitive-behavioral therapy, can reduce reports of pain. Although these are complex procedures, one important variable common to each is direction of attention. We have previously demonstrated in both humans and monkeys a method for monitoring and manipulating attention toward or away from a painful stimulus and have shown that changes in the direction of attention alter the abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
171
3
4

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(201 citation statements)
references
References 27 publications
23
171
3
4
Order By: Relevance
“…The mean number of participants who handed in a diary every week (one page per week) was 18 (range [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The first three weeks 26, 22, and 23 participants, respectively, handed in a diary.…”
Section: Participantsmentioning
confidence: 99%
“…The mean number of participants who handed in a diary every week (one page per week) was 18 (range [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The first three weeks 26, 22, and 23 participants, respectively, handed in a diary.…”
Section: Participantsmentioning
confidence: 99%
“…Most often studies found a reduction in pain experience (McCaul and Malott 1984;Miron et al 1989;Petrovic et al 2000;Tracey et al 2002;Valet et al 2004;Van Damme et al 2008; but see Goubert et al 2004;McCaul et al, 1992). Directing attention away from pain also dampens the processing of nociceptive input in various brain structures (Bantinck et al 2002;Valet et al 2004;Villemure and Bushnell 2009), in particular through the activation of prefrontal areas (Bantinck et al 2002;Petrovic et al 2000;Valet et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have argued that distraction is effective because attention is directed towards a stimulus from another perceptual modality (McCaul and Malott, 1984;Miron et al 1989;Petrovic et al 2000;Tracey et al 2002;Valet et al 2004). This hypothesis however is premature since distraction tasks used in previous studies involved both (1) directing attention towards a perceptual modality other than nociception and (2) directing attention towards a spatial location other than the location of the painful stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a number of studies have shown that difficult tasks might be more successful in altering pain perception than easier tasks. 3,26,30,36 Hence, attention to a cognitive task might alter pain perception only when task load is sufficiently high.On the other hand, it has been hypothesized that pain perception can modulate attention demanding task performance. 9 Pain is a high-priority signal for danger and threat and therefore draws on limited capacity, which might lead to capacity limits being exceeded and there-…”
mentioning
confidence: 99%
“…Moreover, a number of studies have shown that difficult tasks might be more successful in altering pain perception than easier tasks. 3,26,30,36 Hence, attention to a cognitive task might alter pain perception only when task load is sufficiently high.…”
mentioning
confidence: 99%